Is the ICC making the most of victim participation? - Pena, Mariana (International journal of transitional justice, 2013)
Fifteen years after the adoption of the Rome Statute, which was the first instrument to recognize victims’ right to participate in international criminal proceedings, the article examines the International Criminal Court’s practice regarding the implementation of that right. The authors investigate the rationale for victim participation in criminal proceedings from the optic of a restorative justice approach and submit that improved participation would benefit both victims and the Court. The article offers a critical assessment of the Court’s practice to determine whether it has lived up to its restorative justice mandate.